Assessment of Conflicts of Interest in Robotic Surgical Studies: Validating Author's Declarations With the Open Payments Database. Issue 1 (July 2018) - Patel, Sunil V.; Yu, David; Elsolh, Basheer; Goldacre, Ben M.; Nash, Garrett M.
Abstract : Background: Accurate conflict of interest (COI) statements are important, as a known COI may invalidate study results due to the potential risk of bias. Objective: To determine the accuracy of self-declared COI statements in robotic studies and identify risk factors for undeclared payments. Methods: Robotic surgery studies were identified through EMBASE and MEDLINE and included if published in 2015 and had at least one American author. Undeclared COI were determined by comparing the author's declared COI with industry reported payments found in the "Open Payments" database for 2013 and 2014. Undeclared payments and discrepancies in the COI statement were determined. Risk factors were assessed for an association with undeclared payments at the author and study level. Results: A total of 458 studies (2253 authors) were included. Approximately, 240 (52%) studies had 1 or more author receive undeclared payments and included 183 where "no COI" was explicitly declared, and 57 with no declaration statement present. Moreover, 21% of studies and 18% of authors with a COI declared it so in a COI statement. Studies that had undeclared payments from Intuitive were more likely to recommend robotic surgery compared with those that declared funding (odds ratio 4.29, 95% confidence interval 2.55–7.21). Conclusions: We found that it was common for payments from Intuitive to be undeclared in robotic surgery articles. Mechanisms for accountability in COI reporting need to be put into place by journals to achieve appropriate transparency to those reading the journal article.